2020
DOI: 10.3390/en13123162
|View full text |Cite
|
Sign up to set email alerts
|

Spillovers to Renewable Energy Stocks in the US and Europe: Are They Different?

Abstract: This paper examines the spillovers of return and volatility transmitted from fossil energies (crude oil and natural gas) and several important financial variables (stock market index, bonds, and the volatility index) to renewable stock markets in the US and Europe under the time-frequency domain frameworks. The total spillovers of return and volatility from all variables to renewable stock markets in the US are higher than those in Europe. Stock markets transmit the highest return spillovers to renewable energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 41 publications
3
21
0
1
Order By: Relevance
“…Despite the fact that a wider horizon has a smoothing effect on the results, they manifest a high degree of similarity to the baseline specification. We notice that the overall spillover index is generally higher in turbulent times, which is in line with the findings of studies such as: Andrada-Félix et al [ 21 ], Chau and Deesomsak [ 23 ], Chatziantoniou et al [ 32 ], Liu and Hamori [ 33 ], Barunik et al [ 51 ], Demirer et al [ 52 ], and Marfatia et al [ 53 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Despite the fact that a wider horizon has a smoothing effect on the results, they manifest a high degree of similarity to the baseline specification. We notice that the overall spillover index is generally higher in turbulent times, which is in line with the findings of studies such as: Andrada-Félix et al [ 21 ], Chau and Deesomsak [ 23 ], Chatziantoniou et al [ 32 ], Liu and Hamori [ 33 ], Barunik et al [ 51 ], Demirer et al [ 52 ], and Marfatia et al [ 53 ].…”
Section: Resultssupporting
confidence: 91%
“…Many authors investigate financial market sectoral connectedness [ 21 , 30 , 31 , 32 , 33 ]. For example, Chatziantoniou et al [ 32 ] find that financials, industry or basic materials are net risk transmitters, while IT, consumer goods, healthcare or telecommunications receive most of the risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because volatility is generated after a return, volatility needs more time to transmit from one market to another market. Liu and Hamori (2020) investigated the return and volatility spillover effect transmitted from fossil energies, in terms of several important financial variables, to renewable stock markets, and they also found that most of the return spillover effect concentrates at a high frequency (in the short term), but most volatility spillovers are developed at a low frequency (in the long term).…”
Section: Resultsmentioning
confidence: 99%
“…To obtain the dynamic results of return and volatility, we also employed the moving window method in terms of the time domain approach and the method based on frequency dynamics. Liu and Hamori (2020) used the rolling analysis method to check the dynamic results of return and volatility spillover among renewable energy stocks between the US and Europe. Zhang and Wang (2014) also applied rolling samples to better understand and capture the return and volatility spillover effects in the dynamic relationship between the Chinese and global oil markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Economic uncertainty has a significant impact on renewable energy markets, as observed in several previous studies (Dutta 2017 ; Ahmad and Rais 2018 ; Uddin et al 2019 ). Liu and Hamori ( 2020 ) analyzed the relationship between financial uncertainty and renewable energy stocks. Ji et al ( 2018 ) illustrated the impact of financial uncertainty on clean energy stocks using time-varying copulas.…”
Section: Literature Reviewmentioning
confidence: 99%